Evaluation of the effect of pentoxifylline on the prevention of paclitaxel‑induced peripheral neuropathy in breast cancer patients: a randomized controlled study - Sondos S. Saleh; Diaa Eldin Moussa Sherif; Nagwa A. Sabri; May A. Shawki (SpringerOpen, 2024)
Abstract Background Paclitaxel-induced peripheral neuropathy (PIPN) is one of the most common and debilitating toxicity. Up till now, no treatment or preventive medication is recommended by guidelines. Pentoxifylline has been found to prevent PIPN in animal models. This study aimed to evaluate the tolerability and efficacy of pentoxifylline in preventing PIPN. To our knowledge, this is the first clinical trial to evaluate the potential effect of pentoxifylline on the prevention of PIPN in breast cancer (BC) patients. Results A simple-randomized placebo-controlled study was conducted on 60 BC patients receiving weekly paclitaxel and either pentoxifylline 400 mg twice daily (n = 30) or placebo (n = 30) for 12 weeks. Only 55 patients completed the study. The main objective was the evaluation of the effect of pentoxifylline on the incidence of PIPN which revealed no significant difference between the pentoxifylline group (85%) and the placebo group (100%). Secondary objectives included time to develop grade 2 or 3 (TTG 2/3) PIPN, the patient's quality of life (QOL), serum tumor necrosis factor-α (TNF-α) and malondialdehyde and the tolerability of pentoxifylline. The median TTG 2/3 PIPN was not reached in the pentoxifylline group compared to 77 days (95% confidence interval of 70.91 to 83.07) in the placebo group. However, the difference did not reach significance. The assessment of the impact of PIPN on QOL was performed at baseline and at weeks 4, 8 and 12 using Functional Assessment of Cancer Therapy/Gynecologic Oncology Group-Neurotoxicity (FACT/GOG-NTX) subscale. The magnitude of the worsening in the QOL was significantly lower in the pentoxifylline group than in the placebo group at weeks 4, 8, and 12 (p values = 0.028, 0.003, and 0.018, respectively). Analysis of the serum TNF-α and malondialdehyde revealed no significant differences between the groups. Pentoxifylline was safe, tolerable and did not affect paclitaxel toxicity. Conclusion Oral pentoxifylline (400 mg twice daily) did not decrease the incidence of PIPN. However, it improved patients' QOL significantly. Trial registration Clinical Trials.gov, NCT05189535. Registered 4 October 2021, https://classic.clinicaltrials.gov/ct2/show/NCT05189535 .